The Minimum Wage Puzzle in Less Developed Countries : Reconciling Theory and Evidence - Adam, Christopher (IMF Working Papers; Working Paper ;, 2020)
We show that a dynamic general equilibrium model with efficiency wages and endogenous capital accumulation in both the formal and (non-agricultural) informal sectors can explain the full range of confounding stylized facts associated with minimum wage laws in less developed countries.